The Correlation between Writing Medical Terminology Accuracy with the Accuracy of Typhoid Fever Diagnosis Codes for Inpatients - Rahmawati, Eni Nur; Yatim, Nurulshyha Md; Hasanah, Pangestuti ‘Ainun; Sari, Sella Yulia (Global Health Science Group, 2024)
The accuracy of writing medical terminology can affect the accuracy of coding because if the code written by the doctor is not clear, the coder will have difficulty determining the diagnosis code and this can hamper the data processing process in the hospital. Based on the results of the initial survey, the level of accuracy in writing medical terminology was 40% and coding accuracy was 80%. This study aims to determine the relationship between the accuracy of writing medical terminology and the accuracy of typhoid fever diagnosis codes. Type of analytical research with a cross-sectional approach design. The total population is 312 documents with a sample of 175 medical record documents. Simple random sampling technique. Observation and interview data collection techniques. This research instrument is an observation guide, interview guide, checklist, and ICD-10. The results of the research on the accuracy of writing medical terminology were 78 documents (44.57%) and the inaccuracy of writing was 97 documents (54.43%). Inaccuracies are due to not being by the writing in ICD-10, namely 14 documents (14.43%), not complying with the list of abbreviations at the hospital 33 documents (34.02%), and inaccuracies due to the use of Indonesian, namely 50 documents (51.55%). The accuracy of typhoid fever case codes was 141 documents (80.57%) and code inaccuracies were 34 documents (19.43%). Inaccuracy due to incorrect assignment of the fourth character code. The results of the chi-square test showed that the p-value was 0.000<0.05, which means there is a relationship between the accuracy of writing medical terminology and the accuracy of the typhoid fever diagnosis code in inpatients at PKU Muhammadiyah Hospital, Surakarta. Suggestions for the head of medical records are to create an SOP or standing procedure regarding writing appropriate and consistent medical terminology by ICD-10 and a list of abbreviations, so that there is agreement between doctors and medical records officers.